Impacts of El Niño on the South China Sea surface salinity as seen from satellites. (1st May 2022) - Qi, Jifeng; Du, Yan; Chi, Jianwei; Yi, Daling Li; Li, Delei; Yin, Baoshu
Abstract: The impacts of El Niño on sea surface salinity (SSS) in the South China Sea (SCS) are investigated using satellite observations, in-situ data, and reanalysis products. Here, we show that positive SSS anomalies cover most of the SCS during the mature phase of El Niño. The physical processes controlling these positive SSS anomalies are different from region to region, and the differences are especially obvious between the northern and southern SCS. In the northern SCS, the positive SSS anomalies are primarily caused by horizontal advection in response to an enhanced Kuroshio intrusion through the Luzon Strait, while changes in surface freshwater fluxes act to reduce SSS. In the southern SCS, the positive SSS anomalies are largely due to reduced surface freshwater fluxes, with ocean dynamics playing a secondary role. An anomalous anticyclone associated with El Niño is mainly responsible for the reduction of surface freshwater fluxes in the southern SCS.